2013
DOI: 10.3389/fendo.2013.00086
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity and Gender Role in DSD Patients Raised as Females: A Preliminary Outcome Study

Abstract: Gender identity and gender role are expected to be consistent with gender assignment for optimal DSD management outcome. To our knowledge, our study is the first to attempt evaluation of gender related outcomes in Turkish DSD patients. After receiving institutional ethical board approval and subject (or parent) informed consent, subjects with DSD raised as girls (22 patients 46 XX DSD, 11 patients 46 XY DSD) answered 566 questions of the Minnesota Multiphasic Personality Inventory (MMPI) questionnaire includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It can result in the individual being ostracized from all socio-familial events. One-third of 46 XX patients with disorders of sexual differentiation (DSD) tend to experience gender dissonance [3] with their biological sex.…”
Section: Introductionmentioning
confidence: 99%
“…It can result in the individual being ostracized from all socio-familial events. One-third of 46 XX patients with disorders of sexual differentiation (DSD) tend to experience gender dissonance [3] with their biological sex.…”
Section: Introductionmentioning
confidence: 99%
“…According to many authors, the primary goal in DSD was for gender identity to be consistent with the gender assigned and to avoid a gender assignment that would increase the risk of GD [25,35]. In fact, although there is no clear manifestation of GD, it has been reported that both individuals with 46,XX (27.3 %) and 46,XY (45.5 %) may show a discomfort with their gender identity [63]. For many years, according to the "optimal gender policy" developed by Money [11,64], it was believed that gender identity should have been concordant with assigned sex, assuring that the child is raised unambiguously and that appropriate surgical "corrections" and hormone therapies are instituted in line with the gender chosen.…”
Section: Gender Assignment In Dsdmentioning
confidence: 99%
“…Defective conversion of 17-hydroxyprogesterone to 11-deoxycortisol (CYP21 deficiency) accounts for more than 90 % of cases of CAH [110]. Psychosocial assessments have demonstrated that CAH women, when compared to controls, report more cross-gender typical role behavior and patterns during childhood [25, 63,111,112], with a preference for typically male toys [24, [111][112][113][114][115][116] and playmates [25,114]. Moreover, it has been reported that they are less interested in maternal rehearsal play, feminine makeup, and accessories [115,117,118].…”
Section: XX Dsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies include reports by people with DSD who identify neither as male nor female, or who identify as both male and female at different times in their lives. This inability of binary (male/female) gender categories to adequately describe gender identity is more common in people with DSD who possess a Y chromosome [54,57].…”
Section: Gender Assignmentmentioning
confidence: 99%